GAMELAN DEGUNG SEBAGAI SARANA PENGIRING PROSESI TARI PANGBAGEA PADA WISUDA KE XVI STSI BANDUNG TAHUN 2012 - Mulyana, Kari (LP2M ISBI Bandung, 2018)
An idea of karawitan cultivation in gamelan degung is the realization of imagination and expression of the soul based on the experience of a cultivator/ stylist who is applied to a claim. In this case the gamelan gamelan is functioned as an accompaniment of the